2018
DOI: 10.1039/c8dt00106e
|View full text |Cite
|
Sign up to set email alerts
|

Aero-gel assisted synthesis of anatase TiO2 nanoparticles for humidity sensing application

Abstract: Aero-gel based one-pot synthesis of anatase phase TiO2 nanoparticles having a high surface area of 125 m2 g-1 has been reported in this work. The humidity sensing perfomance of the obtained porous TiO2 nanoparticles exhibits a quick response (2 s) and fast recovery (1.5 s), negligible hysteresis (<1%) and good stability in the 11-98%RH range. The relationship between %RH and resistance was found to be linear while the sensitivity increases with increase in %RH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The N 1s spectrum demonstrates three distinct peaks at 398.6, 399.8, and 401.5 eV, which respectively correspond to the nitrogen bonding of sp 2 hybridized aromatic nitrogen in CN–C, ternary nitrogen in (N–(C) 3 ), and heptazine bonding with −NH or −NH 2 groups . The XPS spectra of Ti 2p illustrate that the peaks at 458.4 and 463.9 eV respectively denote the binding energies for Ti 2p 1/2 and Ti 2p 3/2 electrons and justify the existence of Ti 4+ in the TiO 2 crystal lattice . The Au 4f core-level XPS spectrum displays doublet peaks at 83.2 and 87.4 eV, which respectively correspond to the Au 4f 7/2 and Au 4f 5/2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The N 1s spectrum demonstrates three distinct peaks at 398.6, 399.8, and 401.5 eV, which respectively correspond to the nitrogen bonding of sp 2 hybridized aromatic nitrogen in CN–C, ternary nitrogen in (N–(C) 3 ), and heptazine bonding with −NH or −NH 2 groups . The XPS spectra of Ti 2p illustrate that the peaks at 458.4 and 463.9 eV respectively denote the binding energies for Ti 2p 1/2 and Ti 2p 3/2 electrons and justify the existence of Ti 4+ in the TiO 2 crystal lattice . The Au 4f core-level XPS spectrum displays doublet peaks at 83.2 and 87.4 eV, which respectively correspond to the Au 4f 7/2 and Au 4f 5/2 .…”
Section: Resultsmentioning
confidence: 99%
“…40 The XPS spectra of Ti 2p illustrate that the peaks at 458.4 and 463.9 eV respectively denote the binding energies for Ti 2p 1/2 and Ti 2p 3/2 electrons and justify the existence of Ti 4+ in the TiO 2 crystal lattice. 41 The Au 4f core-level XPS spectrum displays doublet peaks at 83.2 and 87.4 eV, which respectively correspond to the Au 4f 7/2 and Au 4f 5/2 . Moreover, the splitting energy between the two peaks is equal to 3.2 eV, which denotes the presence of metallic gold (Au 0 ) according to the standard spectrum of Au, which is in good agreement with the Handbook of X-ray Photoelectron Spectroscopy.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Li et al also produced an ultrasensitive humidity sensor using TiO 2 nanowires that are connected to Ti 3 C 2 , utilizing the cross-linked structure to improve the conductivity [ 9 ]. Ultrafine TiO 2 nanoparticles (4 to 15 nm) synthesized using the aero-gel method resulted in an excellent sensing performance due to its porous nature and large interlayer distance [ 10 ]. Meanwhile, Wang et al [ 11 ] reported that an urchin-like CuO nanostructure produced a remarkable humidity sensing response due to the capillary condensation process, facilitated by the gap existing between the spine structures.…”
Section: Introductionmentioning
confidence: 99%
“…Fig. 3b depicts O 1s core-level region with two peaks; the peak around 529.67 eV was accredited to lattice oxygen and the one located at 531.70 eV was attributed to the surface hydroxyl group [22]. Fig.…”
Section: Introductionmentioning
confidence: 99%